2016
DOI: 10.3390/ijerph13111140
|View full text |Cite
|
Sign up to set email alerts
|

Care-Seeking for Diarrhoea in Southern Malawi: Attitudes, Practices and Implications for Diarrhoea Control

Abstract: This paper examined care-seeking behaviour and its associated risk factors when a family member had diarrhoea. Data was obtained from a survey conducted in Chikwawa, a district in Southern Malawi. Chikwawa is faced with a number of environmental and socioeconomic problems and currently diarrhoea morbidity in the district is estimated at 24.4%, statistically higher than the national average of 17%. Using hierarchically built data from a survey of 1403 households nested within 33 communities, a series of two lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…This could be explained by the fact that there are effective homemade treatments for diarrhoea such as ORS. The efficacy of this cost effective solution which only requires salt, sugar and clean water may have made it unnecessary to seek further medical care for this sickness, as was also observed in a study from southern Malawi [30]. Additionally, a study conducted in the northern part of Nigeria revealed that people who participated in an ORS knowledge programme demonstrated better skills for managing diarrhoea at home than people who did not participate [31].…”
Section: Relevance Of Resultsmentioning
confidence: 72%
“…This could be explained by the fact that there are effective homemade treatments for diarrhoea such as ORS. The efficacy of this cost effective solution which only requires salt, sugar and clean water may have made it unnecessary to seek further medical care for this sickness, as was also observed in a study from southern Malawi [30]. Additionally, a study conducted in the northern part of Nigeria revealed that people who participated in an ORS knowledge programme demonstrated better skills for managing diarrhoea at home than people who did not participate [31].…”
Section: Relevance Of Resultsmentioning
confidence: 72%
“…54 A 2016 study in southern Malawi revealed that a higher proportion (68%) of women with children with diarrhea reported administering ORT at home, whereas 14% gave the children other fluids and only 13% visited a health facility. 55 In addition, women may regard diarrhea as a minor ailment 56 which can be easily managed at home without incurring further costs by visiting health facilities. Prior health service utilization was associated with increased odds of both treatment-seeking behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…23 These results indicate the importance of health education messages on the use and efficacy of ORS to ensure proper and prescribed handling in the management of diarrhoea. 24 Furthermore, it is important to follow the recommendations in the management of acute diarrhoea strictly, since indiscriminate usage of drugs results in the development of resistance if an antibiotic is added to the management regimen. The addition of so-called harmless but unnecessary drugs shifts the emphasis from the standard management of childhood diarrhoea, which includes ORS, feeding, and zinc supplementation.…”
Section: Discussionmentioning
confidence: 99%